Можливості судових експертиз під час розслідування незаконного обігу зброї - Андрєєв, Д. В.; Andrieiev, D. V. (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 3 (78). - С. 45-51, 2017)
Поняття «незаконний обіг зброї» охоплює комплекс правопорушень, які передбачені чотирнадцятьма статтями Кримінального кодексу України. Всі злочини об’єднує один предмет злочину, яким є зброя. Під час розслідування цих злочинів обов’язково призначається експертиза зброї та слідів і обставин її використання. Різноманітність видів зброї і способів учинення злочинів обумовлює необхідність призначення інших судових експертиз.

The term of “illegal weapons trafficking” includes a set of offenses, which are provided for by fourteen articles of the Сriminal Сode of Ukraine. The indicated crimes include the following actions with weapons: moving across the customs border of Ukraine outside customs control or with concealment from customs control; abduction, appropriation, extortion, taking possession by fraud or abuse of office; illegal possession, storage, acquisition, transfer, sale, manufacturing, repair; processing, falsification, deletion or change of marking; careless storage; violation of the rules of storage, use, accounting, transportation, handling; illicit traffic on an aircraft; intentional or careless destruction or damage; loss or damage; development, production, acquisition, storage, distribution, transportation. All of these offenses combine one crime subject, which is a weapon, including ammunition, explosives and devices. The investigation of these crimes calls for the use of specialized knowledge in the form of forensic expertise. The forensic expertise of the weapon, traces and conditions of its use, which allows to determine the crime subject, is mandatory. The variety of weapons types and methods of committing crimes determines the conduct of other forensic expertise. The examination of documents is carried out in the forensic expertise of handwriting and technical expertise of documents. The oral speech of the participants in the crime is examine in the linguistic expertise of oral speech and the expertise of video and audio records. Trasology expertise provides an opportunity to identify destroyed relief marks on weapons, the belonging of individual parts to one copy of the weapon, the presence of fingerprints on the weapon. With the help of a portrait expertise, a person whose appearance is fixed on a photo or video is identified. Expertise of materials, substances and products is assigned to identify the materials from which weapons were made, as well as the detection of micro particles of explosives. Art expertise is conducted to determine the historical and cultural value of antiquarian weapons.

Понятие «незаконный оборот оружия» охватывает преступления, предусмотренные четырнадцатью статьями Уголовного кодекса Украины. Все преступления объединяет один предмет преступления, которым является оружие. При расследовании этих преступлений обязательно назначается экспертиза оружия и следов и обстоятельств его использования. Разнообразие видов оружия и способов совершения преступлений обусловливает необходимость назначения иных судебных экспертиз.
The possibilities of forensic expertise in the investigation of illegal weapons trafficking
Возможности судебных экспертиз при расследовании незаконного оборота оружия
Андрєєв, Д. В. Можливості судових експертиз під час розслідування незаконного обігу зброї / Д. В. Андрєєв // Вісник Харківського національного університету внутрішніх справ. - 2017. - № 3 (78). - С. 45-51.
Andreev, D.V. (2017), “The possibilities of forensic expertise in the investigation of illegal weapons trafficking” [Mozhlyvosti sudovykh ekspertyz pid chas rozsliduvannia nezakonnoho obihu zbroi], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 3, pp. 45–51.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; незаконний обіг зброї; спеціальні знання; судові експертизи; зброя; illegal weapons trafficking; special knowledge; forensic expertise; weapons; незаконный оборот оружия; специальные знания; судебные экспертизы; оружие